Dukungan Keluarga dalam Proses Pemulihan Anggota Keluarga yang Mengalami Gangguan Jiwa - Widya Satuwo; Suhermi; Haeril Amir (Window of Nursing Journal, 2026)
According to World Health Organization data, 450 million people worldwide suffer from mental disorders, which are estimated to affect one in every four people. Mental disorders are a major global health problem. Emotional health is an important part of a person's life, because with a healthy mind, people can grow ideally in physical, intellectual, and social aspects, cooperate with their environment, and deal with their own and their family's problems. Family support is the belief that helpers are always ready to provide assistance and immediate care when any family member is sick. It also includes the attitudes, actions, and acceptance of family members toward the sick member. The purpose of this study is to find out the relationship between family support and the recovery process of family members experiencing mental disorders at Tamamaung Health Center in Makassar City. This research uses a quantitative analytic observational design with a cross-sectional approach. The sample selection was done using purposive sampling, with 40 patients chosen based on inclusion and exclusion criteria. The results of this study showed that 12.5% had good family support, and 80% of the patients recovered. The study also showed that there is a relationship between family support and the recovery process of members experiencing mental disorders (ρ = 0.006 < α 0.05). The conclusion of this study is that there is a significant relationship between family support and the recovery process of family members experiencing mental disorders at Tamamaung Public Health Center in Makassar.